Factors that influence consumer behavior towards telecommunication operators: a case study at DiGi Shah Alam / Siti Fadilah Mohd Rusli - Mohd Rusli, Siti Fadilah (2015)
Mobile number portability is now a crucial issue for mobile services providers. Today, the most challenging job for the present day is that to retain existing mobile customers. The mobile operator’s ability to maintain its customer has a direct impact on its profitability and effectiveness. Losing a customer will affect the mobile operators in terms of cost. Assuming that services quality, prices, promotions and social are the factors that influence consumer behavior towards the telecommunication operators in DiGi. Regards to the research, it will identify the most relevant factor that affecting consumer behavior. Then the most relevant factor will be determined as essential factor that can create customer base towards the telecommunication operators in DiGi at Shah Alam. In order to collect the data, it is assuming by distributing 100 questionnaires to every individual that using DiGi as their telecommunication operator services in Shah Alam. Furthermore, the study is conducting to enhance knowledge about the factors that influence the consumer behavior. A descriptive study will be done in Shah Alam.